STRATEGI MANAJEMEN KURIKULUM DALAM RANGKA PELAYANAN PEMBELAJARAN DAN PENINGKATAN KOMPETENSI PESERTA DIDIK DI SMPN 2 KEDUNGWARINGIN - Qotrunnada, Laila; Ajat Rukajat; Chairil Fajar Hardiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe curriculum management strategies in improving learning services and student competence at SMPN 2 Kedungwaringin. The study used a descriptive qualitative approach through field observation, interview, and documentation study. The main focus included curriculum planning, organization of learning, classroom implementation, monitoring and evaluation, as well as documentation and innovation in curriculum development. The findings indicate that the school has developed the Kurikulum Operasional Satuan Pendidikan (KOSP) based on the school vision, mission, and local context. Teachers have begun to apply varied learning methods, including discussion, student presentation, visual media, and limited use of digital technology. However, several aspects still need improvement, particularly the availability of learning resources, the implementation of the Pancasila Student Profile Strengthening Project, literacy and numeracy programs, and systematic digital documentation of supervision results. The study concludes that curriculum management at SMPN 2 Kedungwaringin has been implemented in a participatory and relatively structured manner, but strengthening teacher capacity, facilities, and evaluation documentation is still needed to improve learning quality and student competence.